Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ctr.14477
|View full text |Cite
|
Sign up to set email alerts
|

Video education to facilitate patient outreach about living kidney donation: A proof of concept

Abstract: Background Increasing living‐donor kidney transplantation (LDKT) requires education of transplant candidates and their social network. This pre‐post study tested the feasibility and acceptability of KidneyTIME, an intervention which leverages LDKT video‐based educational content designed for sharing. Methods Adult kidney candidates undergoing transplant evaluation/re‐evaluation and their caregivers at a single transplant center viewed different sets of KidneyTIME videos prior to evaluation. Change in LDKT know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The videos were informed by health communication and multimedia best practices and iteratively developed with feedback from a diverse group of kidney failure patients and their social network members. A pre-post study showed the videos were promising to increase knowledge across groups of different races [23]. However, the extent to which the video education responds to LDKT cognitive and communication barriers reported specifically by Black individuals is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The videos were informed by health communication and multimedia best practices and iteratively developed with feedback from a diverse group of kidney failure patients and their social network members. A pre-post study showed the videos were promising to increase knowledge across groups of different races [23]. However, the extent to which the video education responds to LDKT cognitive and communication barriers reported specifically by Black individuals is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The videos were informed by health communication and multimedia best practices and iteratively developed with feedback from a diverse group of kidney failure patients and their social network members. A pre-post study showed the videos were promising to increase knowledge across groups of different races [ 24 ]. However, the extent to which the video education responds to LDKT cognitive and communication barriers reported specifically by Black individuals is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Animated video is a powerful medium to deliver information and can be deployed as standalone education 13–17 . Animated video can bring education to people and is easy for anyone to deliver, including administrative staff and lay intermediaries; it can also greatly improve the quality of information while addressing many of the root causes for poor information access, such as language and literacy barriers.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Since 2018, we have been developing an animated-video curriculum (called KidneyTIME) to increase kidney transplant access with an emphasis on living kidney donor transplantation. 17 Participant feedback during video formative and development work indicated the need to add content to empower patients to be referred to a transplant center, and resulted in 8 new videos being produced and added to the intervention curriculum. Our intervention development is guided by an agile scientific framework for producing a product and testing hypotheses, 19 which includes a series of feasibility and usability studies testing each intervention component that is the smallest meaningful and self-containing entity and making improvements iteratively.…”
mentioning
confidence: 99%
See 1 more Smart Citation